Min-Max Fine Heaps - Nath, Suman Kumar; Rezaul Alam Chowdhury; Kaykobad, M (arXiv.org, 2000)
In this paper we present a new data structure for double ended priority queue, called min-max fine heap, which combines the techniques used in fine heap and traditional min-max heap. The standard operations on this proposed structure are also presented, and their analysis indicates that the new structure outperforms the traditional one.